Harnessing Ethylene and Brassinosteroids for Enhanced Agricultural Productivity and Food Quality - Neelesh Kumar Maurya; Neeti Kushwaha; Pratibha Arya; Gayatri Ramachandra (International Journal of Trends in Horticulture, 2024)
This study provides a comprehensive review of the roles of ethylene and brassinosteroids, two vital hormonal regulators in plants, focusing on their impact on fruit ripening, stress responses, and overall plant growth. Ethylene, a gaseous plant hormone, is recognized as a key regulator in various physiological processes, particularly in the maturation of fruits. Its involvement in the ripening process has profound implications for agricultural practices, as it directly influences the postharvest quality, shelf life, and nutritional value of fruits. Research indicates that managing ethylene levels can significantly extend the shelf life of perishable commodities while maintaining their sensory attributes and nutritional benefits. Ethylene acts by promoting the expression of genes associated with ripening, leading to a cascade of biochemical and physiological changes such as softening, color change, and the development of flavor compounds. Moreover, ethylene plays a crucial role in plant responses to environmental stresses, including biotic and abiotic factors. It modulates defense mechanisms, helping plants adapt to stress conditions such as drought, flooding, and pathogen attacks. The hormone initiates a variety of stress-responsive pathways, enhancing the plant's ability to withstand adverse conditions. By understanding the dual role of ethylene in both promoting ripening and mediating stress responses, strategies can be developed to improve crop resilience and productivity. In addition to ethylene, brassinosteroids are recognized as essential growth-promoting hormones that regulate a range of developmental processes in plants. They are known to enhance cell elongation, division, and differentiation, making them critical for proper plant growth and development. Brassinosteroids operate by binding to specific receptors, such as BRI1, and activating downstream signaling pathways that modulate gene expression. This process not only promotes cell expansion and elongation but also enhances overall plant vigor and health. Research has shown that brassinosteroids improve photosynthetic efficiency, contributing to greater biomass accumulation and yield. This is particularly important in the context of sustainable agriculture, where increasing crop productivity while minimizing environmental impact is a key goal. The ability of brassinosteroids to enhance stress tolerance further underscores their importance in agricultural applications, as they can help plants cope with challenging environmental conditions. Understanding the intricate roles of ethylene and brassinosteroids in plant physiology presents opportunities for advancing agricultural practices and food technology. By leveraging these hormones, researchers and farmers can develop innovative strategies to enhance crop quality, increase yields, and improve the nutritional content of food products. This knowledge is crucial for addressing the challenges of food security and sustainability in a rapidly changing environment. In summary, ethylene and brassinosteroids are pivotal in regulating fruit ripening, promoting growth, and enhancing stress responses in plants. Their comprehensive study is essential for optimizing agricultural practices, ensuring food quality, and contributing to sustainable agricultural development.
Keywords: Brassinosteroids; Cell differentiation; Ethylene; Food quality; Fruit ripening; Growth regulation; Photosynthetic efficiency; Stress response